THE UNBREAKABLE BOND BETWEEN POET AND DRAFT: ANALYZING ALEXANDER FAYNBERG’S ODE TO DRAFTS - Mirag'zamova Oysha Mirsherzod qizi (TADQIQOTLAR, 2025)
Abstract: This research paper explores Ode to Drafts (Qoralamalar Qasidasi) by Alexander Faynberg, a thought-provoking poem that delves into the intimate relationship between a poet and their drafts. Through an in-depth analysis of Faynberg’s use of symbolism, repetition, and philosophical reflections, this paper uncovers the deeper meaning behind the poet’s reverence for the creative process. The poem portrays drafts as not merely preliminary versions of literary works but as living, breathing entities that embody the poet’s struggles, triumphs, and truths. By closely examining key lines, this study highlights how Faynberg elevates the role of drafts from mere writing exercises to sacred artifacts of artistic and spiritual devotion. The full translated version of the poem is included to provide a comprehensive basis for analysis.